Analisis Efektivitas Penerimaan Pajak Daerah dan Kontribusinya Terhadap Pendapatan Asli Daerah Kota Padang (2020-2023) - Hidayatullah, Siti Rahmi; Nuraini, Miranda; Syawitri, Afriosa; Indra, Irma Suryani (Paradoks : Jurnal Ilmu Ekonomi, 2025)
This study aims to analyze the effectiveness and contribution of hotel tax, restaurant tax, entertainment tax, street lighting tax, and BPHTB to the Original Regional Income of Padang City during the 2020-2023 period. This study uses a quantitative approach with descriptive statistical methods. The data used are the financial reports of the Padang City Government for the 2020-2023 period. The results of the study show that the average effectiveness of hotel tax and restaurant tax revenues is above 100% with the category "Very Effective". Meanwhile, the effectiveness of entertainment tax is in the category "Quite Effective" with an average of 80.74%, then the effectiveness of street lighting tax is in the category "Effective" with an average of 97.10%, and BPHTB with an average revenue effectiveness of 39.85% with the category "Not Effective". Furthermore, the average contribution of hotel tax, restaurant tax, and entertainment tax to the Original Regional Income (PAD) of Padang City is below 10% with the category "Very Less". Meanwhile, street lighting tax and BPHTB contributed 19.61% and 15.24% respectively and were included in the “Medium” category.